THE INFLUENCE OF HOTEL MANAGEMENT POLICIES AND MARKETING STRATEGIES ON CUSTOMER TRUST TO STAY AT THE SUTOMO GUEST HOUSE MEDAN HOTEL IN THE COMING TIME (POST COVID-19 PANDEMIC) - Reja Ferdynanta; Elisabet Tambunan (JURNAL MUTIARA MANAJEMEN, 2020)
2020 is a very difficult year for some countries due to the Covid-19 virus outbreak that has hit countries around the world. Covid-19 is a virus originating from China, precisely in the city of Wuhan. This virus has a very fast transmission, as a result of which many citizens of the country are quickly infected by this virus. The government in a number of countries, especially Indonesia, applies social restrictions and calls for all activities from home. As a result, the tourism sector has experienced a significant decline. This study entitled "The Effect of Hotel Management Strategies and Marketing Strategies in Increasing Public Trust to Stay at Sutomo Guest House. Have a problem formulation of how management policies and marketing strategies are able to increase guest confidence to stay at the Sutomo Guest House post-pandemic.This study uses a quantutative method. The data source used is questionnaire data taken from respondents / samples at Hotel Sutomo Guest House. The data will be analyzed using the SPSS application.Based on the data analysis, it is concluded that management policy (X1) and marketing strategy (X2) have a significant effect on increasing consumer confidence (Y) to stay at the Sutomo Guest House hotel. The effect of variable X is 29.4% and 71.6% is another variable not examined in this study.